Lifestyle Migration - McGarrigle, Jennifer (2022)
In the context of the growing global middle class, and the ageing of the baby boomer generation, an increasing number of migrants with accumulated wealth from advanced economies are relocating to economically less developed or more peripheral countries to improve their quality of life. Migration of the middle-classes and the relatively affluent is embedded in the same globalising processes and social transformations in production and processes of accumulation that have reshaped labour migration (Hayes, 2021; Castles, 2010). Privileged mobilities are part of wider migration systems, however, what distinguishes lifestyle migrants from other migrants, who are also in pursuit of a better quality of life, is the ease with which they can relocate due to relative privilege in terms of citizenship and financial or cultural capital.